50 Years On : Probing the Riches of Vatican II - Schultenover, David G., 1938- (Book collections on Project MUSE., 2015)
"Pope John XXIII prayed that the Second Vatican Council would prove to be a new Pentecost. The articles gathered here appeared originally in a series solicited by and published in Theological Studies (September 2012 to March 2014). The purpose of the series was and remains threefold: to commemorate the 50th anniversary of the Second Vatican Council ; to assist in appropriating the reform envisioned by Pope John XXIII; [and] to help readers more fully appreciate its significance not only for the Catholic Church itself but also for the entire world whom the Church encounters in proclamation and reception of ongoing revelation"--Cover.